Comparison of pulsed low level laser therapy and pulsed ultrasound therapy in the treatment of episiotomy - HEMA SWAROOPA.N,; G. DEEPTHI, (International Journal of Pharma and Bio Sciences, 2017)
An episiotomy is an incision made in the perineum (the area of the skin between the vaginal opening and the rectum) during delivery to enlarge the opening for the baby. This incision causes pain and healing will be delayed due to unfavourable perineal environment. In physiotherapy pulsed Low Level Laser Therapy and pulsed Ultra Sound Therapy are more pronounced for enhancing pain reduction favors healing. This study was conducted to compare the effect of pulsed low level laser therapy (LLLT) and pulsed ultra sound therapy (UST) on episiotomy wound healing and pain relief. Twenty subjects were taken from obstetric ward and they were equally divided in to two groups. Group A received pulsed LLLT,Group B received pulsed UST for 7 days. REEDA(Redness,Edema,Ecchymosis,Discharge,Approximation) Scale and (Numeric Pain Rating Scale) was used as a outcome measure. The readings were taken before and after the 7 days of treatment. This study showed statistically significant improvement in healing for both the groups. Group A (p<0.0001), Group B (p<0.0001) for REEDA Scale and significant early pain reduction for Group A treated with pulsed LLLT (P<0.0001), Group B treated with pulsed UST (P=0.0011) for NPRS.